Dwi Chagi Kick Reaction Speed Training Model based on Electronic Body Reaction in Taekwondo Athletes Aged 14-16 Years - Ghoni, Abdul; Fachrezzy, Fahmy; Asmawi, Moch; Susianti, Evi; Jariono, Gatot (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2024)
This study aims to help solve the weaknesses in kicking skill training Dwi Chagi. It can also provide theoretical benefits in kicking exercises Dwi Chagi and practical benefits for researchers, institutions, coaches, athletes, and general readers. Researchers in this paper are working on model development, trying to create and innovate on the design of reaction rate-based training models for electronic body reactions, existing or new, to solve a problem. As with kick training Dwi Chagi, research and development (Research & Development) will produce a reaction speed-based training model product electronic body reaction on kicking skill training Dwi Chagi for taekwondo athletes aged 14-16 years. This research is intended to produce a new and valuable addition to the advancement of science in Taekwondo, especially in exercise, biomechanics, and physiology. This study uses the ADDIE method; in ADDIE, research has five stages: analysis, design, model development, implementation, and evaluation. The research results produced a product in the form of a kick reaction speed training model, a Dwi Chagi-based electronic body reaction. For 14-16 years of taekwondo athletes, it was carried out with 30 male and female athletes. Data was collected through documentation, interviews, and observation activities. Data analysis was carried out descriptively. The research results are in the form of a model book for kick reaction speed training Dwi Chagi-based electronic body reaction. The study's results prove that the training model is quite effective in applying and developing kicking techniques Dwi Chagi.